Dose-resolved serial synchrotron and XFEL structures of radiation-sensitive metalloproteins. (2019) - Ebrahim, Ali; Moreno-Chicano, Tadeo; Appleby, Martin V.; Chaplin, Amanda K.; Beale, John H.; Sherrell, Darren A.
No abstract available